The possibilities and results for the scientific research into the relationship between settlements and sport - Gábor KOZMA; Zoltán BÁCS; Zsombor ZILINYI (Editura Universităţii din Oradea, 2015)
The scope of tasks organised and performed by settlements and their leaders has continuously broadened since the beginnings of time. Initially, the leaders of settlements were primarily expected to provide for the safe operation of the settlement, the creation of the conditions of commerce, as well as the administration of justice. However, from the 18th and 19th centuries onward, settlements started to play an increasingly important role also in the areas of education, social and healthcare services. In the 20th century, parallel with the spread of the notion of the welfare state, activities related to the useful spending of free time have gained importance, among which, in addition to culture - primarily in the most recent times - sports has played an increasingly significant role as well. The aim of this paper is to explore the possible areas of researching the relationships between settlements and sports. Further developing the tetrahedron model of the settlement, the truncated triangular pyramid model has been created, the two bases of which are the natural environment and the municipal administration, while the sides are the infrastructural, economic and social spheres. The paper will present the results of and further possibilities in sports-related research aimed at each of these spheres, as well as the sports-related characteristics of the interactions taking place along the edges of the truncated triangular pyramid.